Pemanfaatan spesimen herbarium sebagai media pembelajaran bagi Guru-Guru IPA/Biologi di Kabupaten Enrekang - Syamsiah Syamsiah; Nurhayati B.; St. Fatmah Hiola (Universitas Negeri Makassar, 2020)
Plant diversity is really important to be a good learning media for students to achieve their goals. Presenting objects directly in class is not easy, therefore herbarium specimens are an alternative. The purpose of Program Kemitraan Masyarakat (PKM) is to provide groups of MGMP / Biology MGMP with understanding and skills in utilizing herbarium specimens as learning media in the classroom. This activities are carried out by lecture, demonstration and question and answer method. The lecture was conducted to explain basic knowledge about the herbarium, and its benefits as a media. The demonstration method was carried out by the instructors to demonstrate how to make a herbarium start from plant selection to pressing. Question and answer method if there is material that is not yet clear. The training on making herbarium as a medium that is used in classroom for Science/Biology teachers group in Enrekang is going well and smoothly; 2) Science / Biology teacher groups as trainees can understand the material well and are skilled in making herbariums starting from the sampling of plants, preservation with alcohol, pressing, drying, until attaching.